Prevalence, associated factors and predictors of depression among adults in the community of Selangor, Malaysia - Kader Maideen, Siti Fatimah; Mohd. Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal; Mukhtar, Firdaus (Public Library of Science, 2014)
Introduction Depression is one of the most common mental health disorders and is an emerging public health problem. The objectives of this paper were to determine the prevalence of depression, its associated factors and the predictors of depression among adults in the community of Selangor. Methods A cross sectional study was conducted in three districts in Selangor, from 11th June to 30th December 2012. The sampling frame was obtained from the Department of Statistics Malaysia (DOS) in May 2012, using the National Population and Housing Census 2010. Adults aged 18 years and above, living in the selected living quarters were approached to participate in the study and requested to complete a set of questionnaires. Results A total of 1,556 out of 2,152 participants participated in this study, giving an overall study response rate of 61.90%. Patient Health Questionnaire 9 (PHQ-9) was used to determine the presence of depression. The prevalence of depression was 10.3%, based on the PHQ-9 cut off point of 10 and above. Based on multiple logistic regression analysis, the predictors of depression were presence of anxiety, serious problems at work, unhappy relationship with children, high perceived stress, domestic violence, unhappy relationship with spouse, low self-esteem, unhappy relationship with family, serious financial constraint and presence of chronic diseases. When reanalyzed after removing anxiety, high perceived stress and low self-esteem, additional predictors of depression were found to be serious marital problems and religiosity. Conclusion The prevalence of depression in this study is similar to that found in other studies. Findings from this study are being used as baseline data to develop an effective program to assist in the management of common mental health disorders in the community, in particular depression. The identification of predictors of depression in the community is important to identify the target population for the program.